Swelling Kinetics and Diffusion Coefficients of Polyacrylamide Hydrogels Via Different Drying Methods - Nazli Ozcan; Didem Saloglu (Journal of Chemical Engineering Research Updates, 2015)
In the present study, polyacrylamide (PAAm) hydrogels were formed by copolymerization of acrylamide (AAm) and N,N' methylenebisacrylamide. The reaction is a vinyl addition polymerization initiated by a free radical generating system. N,N' methylenebisacrylamide, N,N,N',N'-tetramethylethylenediamine (TEMED) and ammonium persulfate (APS) were used as the cross linking agent, catalyzer and initiator, respectively. Hydrogels were dried with two drying methods: the former is the poor solvent method, the latter is the freze dryer method. The effects of the drying methods on swelling behavior were investigated as a function of time. A variety of hydrogel swelling kinetic modelling techniques were applied on the dynamic swelling rates of PAAm hydrogels. For all the hydrogels, the diffusion coefficient of kinetic parameters such as the diffusion mechanism (Fickian or non-Fickian mechanism), initial and equilibrium swelling ratios, the penetration rate of the solvent and diffusion coefficient were determined.